FIRM VALUE PERFORMANCE: PROFITABILITY PERSPECTIVE AND CAPITAL STRUCTURE AT STATE-OWNED BANK - Kendri Nengah Sukendri; Ni Putu Ari Aryawati (Jurnal Aplikasi Akuntansi, 2021)
This study aims to determine the relationship and influence of profitability variables and capital structure on firm value toward BUMN's bank listed stated-owned enterprises 2014-2018 in Indonesia. The method of determining the sample is pooling data that examines the entire population and found as many as 4 companies using multiple linear regression with SPSS 23.0 analysis technique. Based on the results of the analysis found that profitability has a significant effect on firm value. Capital structure has no significant effect on firm value.